2013
DOI: 10.1212/wnl.0b013e3182a55fb9
|View full text |Cite
|
Sign up to set email alerts
|

Priorities in pediatric epilepsy research

Abstract: The Priorities in Pediatric Epilepsy Research workshop was held in the spirit of patient-centered and patient-driven mandates for developing best practices in care, particularly for epilepsy beginning under age 3 years. The workshop brought together parents, representatives of voluntary advocacy organizations, physicians, allied health professionals, researchers, and administrators to identify priority areas for pediatric epilepsy care and research including implementation and testing of interventions designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 58 publications
2
39
0
Order By: Relevance
“…2 Population-based studies on prevalence of epilepsy and comorbid conditions are listed among the priorities for the public health dimension of epilepsy in the recent report issued by the Institute of Medicine (IOM). 3 We previously determined prevalence of epilepsy in Canadian children using Cycles 2 and 3 of National Longitudinal Survey of Children and Youth (NLSCY) data and found our estimates to be comparable to other published studies. 4 In the present study, we extend the analysis to focus on the comorbid conditions associated with epilepsy in children; namely cerebral palsy, mental handicap (intellectual disability), learning disability, emotional and nervous difficulties using data from Cycle 3 which had the largest number of children diagnosed with epilepsy.…”
Section: Introductionsupporting
confidence: 76%
“…2 Population-based studies on prevalence of epilepsy and comorbid conditions are listed among the priorities for the public health dimension of epilepsy in the recent report issued by the Institute of Medicine (IOM). 3 We previously determined prevalence of epilepsy in Canadian children using Cycles 2 and 3 of National Longitudinal Survey of Children and Youth (NLSCY) data and found our estimates to be comparable to other published studies. 4 In the present study, we extend the analysis to focus on the comorbid conditions associated with epilepsy in children; namely cerebral palsy, mental handicap (intellectual disability), learning disability, emotional and nervous difficulties using data from Cycle 3 which had the largest number of children diagnosed with epilepsy.…”
Section: Introductionsupporting
confidence: 76%
“…Both studies suggested that professionals prioritise pharmacological therapy and basic science topics, while paediatric patients and their caregivers prioritised mostly psychosocial health and non-pharmacological treatment, for example, education, diet and lifestyle changes 21 90. We observed a similar trend across all included studies; for example, a study on epilepsy involving only researchers predominantly prioritised aetiology, risk factors and medical therapies,34while another epilepsy-focused study that included parents generated priorities relating to education, patient/provider/community communication, treatment adherence and access to healthcare 89. These results suggest that patient involvement in research priority setting is important in generating a research agenda that encompasses the full spectrum of issues that affect patients.…”
Section: Discussionsupporting
confidence: 61%
“…In one palliative care study, the top priority was ‘ Children’s understanding of death and dying ’,69while an epilepsy study prioritised ‘ What do parents and providers understand about the seriousness of seizures and the need to control them as soon as possible? ’ 89. Education strategies to improve patient,43 52 67 78 83 92 103 healthcare provider45 46 73 83 105 and parent45 46 52 56 64 82 85 89 102 105 knowledge were prioritised.…”
Section: Resultsmentioning
confidence: 99%
“…It has been highlighted that parental engagement in pediatric epilepsy care in terms of communication and shared decision-making represents a crucial factor in the management of this neurological disorder [12]. Still, young persons and their parents feel that medication management of epilepsy is the only priority in a health-care setting [13].…”
Section: Introductionmentioning
confidence: 99%